PENGARUH MOTIVASI KERJA, KEPEMIMPINAN, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI KSP CU LESTARI WONOSOBO - Agustinus Aji Prastyanto, 0935020704 (Students Journal of Economic and Management, 2016)
This research is intended to discover the influences of work motivation, leadership and compensation on the employees performance in the credit union of